The burn patient as a time-dependent entity: an evidence-based practical guide. - O. A, Romero - Arguello; D. E, Meraz - Brenes; J.F, López - Gonzáles; Moreno R., Iribarren; González - Aboytes , J.E; Medina – Preciado , J. D; A. C., Cepeda - Nieto (Revista de Ciencias Médicas Torreón, 2026)
The management of burn patients is time-critical; initial care directly influences the progression of tissue damage, protein coagulation, circulatory disturbances, and necrosis. Key initial interventions include primary assessment using the ABCDE approach, early analgesia, fluid resuscitation, evaluation of injury characteristics and extent, and criteria for timely referral to specialized centers. Thermal burns are the most prevalent (86%), followed by electrical (4%) and chemical (3%) burns, with high global annual morbidity and mortality (11 million affected; 180,000 deaths). It is proposed, practical algorithm is proposed to standardize initial management, optimize decision-making, and improve clinical outcomes for burn patients during the initial care phase.